Normative Values for the Short Physical Performance Battery (SPPB) and Their Association With Anthropometric Variables in Older Colombian Adults. The SABE Study, 2015 - Ramírez-Vélez, Robinson; Pérez-Sousa, Miguel A.; Venegas-Sanabria, Luis C.; Cano-Gutierrez, Carlos A.; Hernández-Quiñonez, Paula A.; Rincón-Pabón, David; García-Hermoso, Antonio; Zambom-Ferraresi, Fabricio; Sáez de Asteasu, Mikel L.; Izquierdo, Mikel (Frontiers in Medicine, 2020)
Background: The short physical performance battery (SPPB) is a physical performance test of lower extremity function designed for non-disabled older adults. We aimed to establish reference values for community-dwelling Colombian adults aged 60 years or older in terms of (1) the total score; (2) the three subtest scores (walking speed, standing balance performance and five repetitions of the sit-to-stand test); and (3) the time to complete the repeated chair sit-to-stand test and the walking speed test. Additionally, we sought to explore how much of the variance in the SPPB subtest scores could be explained by anthropometric variables (age, body mass, height, body mass index, and calf circumference). Methods: Participants were men and women aged 60 years or older who participated in the Health and Well-being and Aging Survey in Colombia, 2015. A sample of 4211 participants (57.3% women) completed the SPPB test, and their anthropometric variables were evaluated. Age-specific percentiles were calculated using the LMS method (3rd, 10th, 25th, 50th, 75th, 90th, and 97th percentiles). Results: The mean SPPB total score for the entire sample was 8.73 (2.0) points. On average, the total SPPB score was 0.85 points greater in men than in women (p<0.001). Significant sex differences were observed in all three age groups tested (60–69, 70–79 and 80+ years). In the full sample, our findings suggested that age, body mass, height, body mass index, and calf circumference are significant contributors to walking speed (p<0.001) after controlling for confounding factors, including ethnicity, socioeconomic status and urbanicity. Conclusions: Percentile values are of interest to identify target populations for primary prevention and to estimate the proportion of high or low values for SPPB measures in community-dwelling Colombians aged at least 60 years.